Permanent draft genome sequence of Vibrio tubiashii strain NCIMB 1337 (ATCC19106). Issue 2 (March 2011) - Temperton, Ben; Thomas, Simon; Tait, Karen; Parry, Helen; Emery, Matt; Allen, Mike; Quinn, John; MacGrath, John; Gilbert, Jack
Abstract Vibrio tubiashii NCIMB 1337 is a major and increasingly prevalent pathogen of bivalve mollusks, and shares a close phylogenetic relationship with bothV. orientalis andV. coralliilyticus . It is a Gram-negative, curved rod-shaped bacterium, originally isolated from a moribund juvenile oyster, and is both oxidase and catalase positive. It is capable of growth under both aerobic and anaerobic conditions. Here we describe the features of this organism, together with the draft genome and annotation. The genome is 5, 353, 266 bp long, consisting of two chromosomes, and contains 4, 864 protein-coding and 86 RNA genes.